Lymphocystis disease virus: its importance in aquaculture - Borrego, Juan Jose; Valverde, Estefania; Labella Vera, Alejandro Manuel; Castro, Dolores (Wiley, 2015)
Lymphocystis disease virus (LCDV) is the causative agent of a well-known fish viral disease that is characterized by hypertrophy of fibroblastic cells in the connective tissue. This viral disease affects more than 125 wild and cultured species of teleost fish from marine and freshwater environments and has a cosmopolitan geographical distribution. In aquaculture systems, the prevalence of LCDV infection is very high, likely reflecting the horizontal transmission of this virus. The incidence rate of the disease may reach 70%, causing significant economic losses for the aquaculture industry. This review provides information on the taxonomy, viral properties, epizootiology and pathogenesis, diagnostic methods and control measures of LCDV infection in fish.
Keywords: Peces - Enfermedades por virus; Acuicultura; Control measures; Diagnostic methods; Lymphocystis disease virus; Pathogenesis